1996
DOI: 10.1074/jbc.271.33.20138
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Interleukin-6 (IL-6) Dimerization on Formation of the High Affinity Hexameric IL-6·Receptor Complex

Abstract: The high affinity interleukin-6 (IL-6) signaling complex consists of IL-6 and two membrane-associated receptor components: a low affinity but specific IL-6 receptor and the affinity converter/signal transducing protein gp130. Monomeric (IL-6 M ) and dimeric (IL-6 D ) forms of Escherichia coli-derived human IL-6 and the extracellular ("soluble") portions of the IL-6 receptor (sIL-6R) and gp130 have been purified in order to investigate the effect of IL-6 dimerization on binding to the receptor complex. Although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
46
0
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 34 publications
3
46
0
1
Order By: Relevance
“…One of the key cytokines is IL-6, which was originally identified as B-cell stimulatory factor-2 and was shown to affect hybridoma growth and also stimulate antibody productivity (Makishima et al 1992). In the proposed mechanism, IL-6 binds to IL-6R and gp130 (Bravo et al 1998;Hibi et al 1990;Muller-Newen et al 2000) to form hexameric complex composed of two molecules of each component (Paonessa et al 1995;Skiniotis et al 2005;Ward et al 1996). This in turn triggers homodimerization and activation of gp130, leading to activation of the Janus kinase family (JAK1, JAK2, TYK2) of signal transducers, which further activate transcription activators (STAT1, STAT3) and mitogen-activated protein kinases (MAP-KKK, MAPKK, MAPK) (Matsuda et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…One of the key cytokines is IL-6, which was originally identified as B-cell stimulatory factor-2 and was shown to affect hybridoma growth and also stimulate antibody productivity (Makishima et al 1992). In the proposed mechanism, IL-6 binds to IL-6R and gp130 (Bravo et al 1998;Hibi et al 1990;Muller-Newen et al 2000) to form hexameric complex composed of two molecules of each component (Paonessa et al 1995;Skiniotis et al 2005;Ward et al 1996). This in turn triggers homodimerization and activation of gp130, leading to activation of the Janus kinase family (JAK1, JAK2, TYK2) of signal transducers, which further activate transcription activators (STAT1, STAT3) and mitogen-activated protein kinases (MAP-KKK, MAPKK, MAPK) (Matsuda et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Recombinant IL-6 D binds tightly to soluble IL-6R (sIL-6R) to form a 1:2 IL-6 D (sIL-6R) 2 complex (16). In contrast to the binary IL-6⅐sIL-6R complex, IL-6 D (sIL-6R) 2 binds gp130 weakly and does not show significant biological activity in the signal transducer and activator of transcription 3 (STAT3) phosphorylation assay (16).…”
mentioning
confidence: 99%
“…Previously, we have shown that a dimeric form of recombinant IL-6 (IL-6 D ) is a potent antagonist for IL-6 signaling (16). Recombinant IL-6 D binds tightly to soluble IL-6R (sIL-6R) to form a 1:2 IL-6 D (sIL-6R) 2 complex (16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The question remained to explain how the lectin activity could participate to the formation of these hexamers. The recombinant soluble form of gp130 used in the previous studies for detecting the formation of hexamers (73)(74)(75)(76) was produced in Chinese hamster ovary cells. This point seems of importance, since these cells are (as HepG2 cancer cell types) competent for the synthesis of the HNK-1 epitope.…”
Section: Importance Of the Lectin Activity Of Il-6 For Its Biologicalmentioning
confidence: 99%